2019
DOI: 10.1016/j.ipl.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A note on degree vs gap of Min-Rep Label Cover and improved inapproximability for connectivity problems

Abstract: This note concerns the trade-off between the degree of the constraint graph and the gap in hardness of approximating the Min-Rep variant of Label Cover (aka Projection Game). We make a very simple observation that, for NP-hardness with gap g, the degree can be made as small as O(g log g), which improves upon the previousÕ(g 1/2 ) bound from a work of Laekhanukit [Lae14]. Note that our bound is optimal up to a logarithmic factor since there is a trivial ∆-approximation for Min-Rep where ∆ is the maximum degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…In addition, we obtain an approximation hardness exponential in k by setting a different parameter in the reduction, which improves upon the previously known approximation hardness of Ω (k/ log k) due to Manurangsi [Man19] (which is in turn based on the two previous results [Lae14, CLNV14]), and is the first known approximation hardness for connectivity problems whose ratio is exponential in the connectivity requirement.…”
Section: Parameter Lower Boundsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, we obtain an approximation hardness exponential in k by setting a different parameter in the reduction, which improves upon the previously known approximation hardness of Ω (k/ log k) due to Manurangsi [Man19] (which is in turn based on the two previous results [Lae14, CLNV14]), and is the first known approximation hardness for connectivity problems whose ratio is exponential in the connectivity requirement.…”
Section: Parameter Lower Boundsupporting
confidence: 71%
“…Manurangsi [Man19] proved that the label cover problem has a hardness gap in terms of the maximum degree of G.…”
Section: (Minimum) Label Cover An Instance Of the Label Cover Problem...mentioning
confidence: 99%
“…In fact, the hardness result holds even when all the connectivity requirements are t0, 1u. The bounds have been improved in the subsequent works to n op1q under Gap-ETH in the work of Dinur [Din16] and has also been refined in [CLNV14,Lae14,DM18,Man19,LCLZ22]. To date, we know that even in the special case of single-source k-connectivity, the problem is at least as hard as the Label-Cover problem [CLNV14], and in the very recent work, Liao, Chen, Laekhanukit and Zhang showed that Directed-SNDP admits no non-trivial approximation algorithms unless NP " ZPP.…”
Section: Related Workmentioning
confidence: 99%
“…That is, no opq{ log qq-approximation algorithm exists unless NP " ZPP, and no opqq-approximation algorithm exists unless the Strongish Planted Clique Hypothesis is false [LCLZ22]. When focusing on the hardness ratio in terms of k, it is shown in [CGL15] (combined with [Lae14] and the improvement in [Man19]) that the approximation hardness is k 1{5´ , for ą 0, assuming NP " ZPP.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation